(untitled) (Punyawati Journal, 2026)
This study examines the impact of service quality explained by front office operation, location, food and beverage, accommodation, recreation and entertainment, pricing on customer satisfaction of beach resorts in Nepal. Descriptive and casual research designs are used for the study. Primary data has been collected through questionnaire survey from guests of different hotels in Sukute beach and Trisuli beach. The study finds that Recreation and Entertainment was the most influential factor determining customer satisfaction, followed by Food and Beverage, Accommodation, and Pricing and Payment. Front Office Operation and Location show limited influence when all predictors are considered together. The findings emphasize the importance of experiential and comfort-related services, offering practical insights for hotel managers aiming to improve overall service quality and enhance guest satisfaction.